A virada retórica implícita de Richard Rorty - Santos, Cauim Ferreira das Neves (2023)
This dissertation aims to attest the implicit affinity of Richard Rorty's neopragmatism with rhetoric. The main goals of this work are: to contextualize and define rhetoric, highlighting the mistaken separation between rhetoric and philosophy, preceded by the anachronistic assimilation between the Sophists' teaching of logos and the rhētorikē created by Plato, correlated with the Sophists' devaluation in contrast to the development of philosophy; to verify the relationship between post-positivist analytical philosophy, and the influence of the linguistic and linguistic-pragmatic turns on the resurgence of rhetoric in 20th century philosophy, and that the radicalization of this movement in analytical philosophy by Rorty's neopragmatism is succeeded by an implicit rhetorical turn.